Immune response to 17 beta-estradiol in polyelectrolyte complex: Antigen specificity and affinity of hybridoma clones - (:unkn) unknown (MARY ANN LIEBERT INC PUBL, 1996)
Complex formation between synthetic polyelectrolytes (PE) [poly-4-vinyl-N-ethyl (cetyl), pyridine bromides-PVP(R(2),R(16))], bovine serum albumin (BSA), or 17 beta-estradiol-BSA conjugate (BSA.E) was studied in neutral water, Weakly water-soluble (colloidal) complex was formed upon addition of BSA.E to PVP (R(2),R(16)) solution at pH 7, A nonrandom distribution of the protein molecules between the coils of polycations and self-assembly in the nonstochiometric polycomplex particles took place, The immunogenic properties of PVP (R(2),R(16))-BSA.E polycomplex were investigated and the specificities of produced antibodies analyzed, 17 beta-Estradiol introduced in polyelectrolyte complexes (PE-BSA) was found to invoke considerable increases in the steroid-specific immunoresponse, However, a comparative study of immunogenic activity of polycomplexes versus BSA.E + incomplete Freund's adjuvant (IFA) mixtures revealed some differences in regards to the specificity of antibody production, In contrast to IFA + BSA.E systems, polycomplexes were able to generate estradiol-as well as BSA-specific antibodies, Such a carrier-directed response may be determined by increase in inmunogenicity of weak antigenic determinants and/or by the exposure of internally located determinants upon complex formation with polyelectrolytes, Fusions following the two different immunization procedures resulted in the growth of comparable numbers of estradiol-specific monoclonal antibodies with apparently similar antigen affinities, Thus, immunizations using antigens in PEC appear to provide an efficient alternative to IFA.